Elliptic flow of Lambda hyperons in Pb+Pb collisions at 158 AGeV - Alt, C.; Antičić, Tome; Baatar, B. Barna, D.; Bartke, J. Betev, L.; Bialkowska, H. Blume, C.; Boimska, B. Botje, M.; Bracinik, J. Bramm, R.; Bunčić, Predrag Cerny, V.; Christakoglou, P. Chvala, O.; Cramer, J.G. Csato, P.; Dinkelaker, P. Eckardt, V.; Flierl, D. Fodor, Z.; et al. (2006)
The elliptic flow of Lambda hyperons has been measured by the NA49 experiment in semicentral Pb+Pb collisions at 158 A GeV. The standard method of correlating particles with an event plane has been used. Measurements of v2 near mid-rapidity are reported as a function of rapidity, centrality and transverse momentum. Elliptic flow of Lambda particles increases both with the impact parameter and with the transverse momentum. It is compared with v2 for pions and protons as well as with models predictions.
Projekt MZOS
ENG